High Performance Three-Dimensional Double-Stacked Multiple-Nanochannel and Quadruple-Nanogate ZnO-Based Fin Metal-Oxide-Semiconductor Field-Effect Transistors. (9th December 2017) - Lee, Hsin-Ying; Jian, Li-Yi; Huang, Hung-Lin; Lee, Ching-Ting
Abstract : To improve performances of zinc oxide (ZnO)-based metal-oxide-semiconductor field-effect transistors (MOSFETs), the double-stacked multiple-nanochannel and quadruple-nanogate (DMCQG) ZnO-based MOSFETs were fabricated using the laser interference photolithography technique and the hardened photoresist technique. The three dimensional double-stacked structure of the ZnO-based fin MOSFETs possessed the same device area as the single structure. However, the drain-source saturation current and the maximum transconductance of the double-stacked MCQG ZnO-based fin MOSFETs were, respectively, improved from 13.7 mA mm −1 to 25.5 mA mm −1 and from 6.9 mS mm −1 to 13.5 mS mm −1 in compared with the single MCQG ZnO-based fin MOSFETs. Besides, the gate leakage current of both the double-stacked structure and the single structure was kept at the order of nA.